Dialogando com o saber matemático em sala de aula - Eveline Vieira Costa (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
This paper analyzes the process in which the teacher creates a problematic communication,in the situation of the classroom, giving students a possible condition for becoming a Subject of the learning, questioning about negotiation of solutions to problems. The teacher's attitude implies an understanding of the value of the place in which they are in the process of recognizing the subject and the importance of this place as a unique place in which learning can start. Here are parameters for this performance. In so doing, the teacher leads the student to become a legitimate member of the school as a community of practice. To support this analysis we examined the dialogical communication of Bakhtim and the difference between sense and meaning in a scientific literature.